2010
DOI: 10.1038/laban1110-342
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of dosages and routes of administration of tramadol analgesia in rats using hot-plate and tail-flick tests

Abstract: Tramadol is an opioid-like analgesic with relatively mild side effects. Because it is inexpensive and is not classified as a controlled substance by the US federal government, the authors wanted to evaluate its applicability as a practical and effective analgesic in male Sprague Dawley rats. They measured the efficacy of four dosages (4, 12.5, 25 or 50 mg tramadol per kg body weight) and three routes of administration (per os (p.o.) in a flavored gelatin cube, subcutaneous (s.c.) or intraperitoneal (i.p.)) usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 27 publications
0
23
0
Order By: Relevance
“…The dosage, route and administration time were established according to the previous studies (Cannon et al, 2010). The evaluation of pain was done across at the time 0, 2, 4 and 6 hours postsurgery.…”
Section: Methodsmentioning
confidence: 99%
“…The dosage, route and administration time were established according to the previous studies (Cannon et al, 2010). The evaluation of pain was done across at the time 0, 2, 4 and 6 hours postsurgery.…”
Section: Methodsmentioning
confidence: 99%
“…The tramadol dose was selected on the basis of several published reports of its effective use in several invasive surgical models in rats [5], [9]. Considering that thoracic pain is one of the most acute among several surgical insults, we chose 45 mg/kg, the highest dose published [8].…”
Section: Methodsmentioning
confidence: 99%
“…Carprofen is a non-steroidal anti-inflammatory drug, which veterinarians prescribe as a supportive analgesic for various painful conditions, including surgery [1]. Tramadol is an opioid-like analgesic with a potent analgesic effects [5]. The goal was to establish which of the three approaches may reduce post-surgical pain and to apply the principle of Reduction to our experimental protocol.…”
Section: Introductionmentioning
confidence: 99%
“…A study conducted on Sprague Dawley rats showed that 60 min after i.p. administration of 12.5 mg/kg tramadol increased latency in the hot plate test, whereas greater doses (25 and 50 mg/kg) caused sedation and affected motor function (Cannon et al, 2010).…”
Section: Discussionmentioning
confidence: 85%